Psychological Impact of Cyber-Bullying: Implications for School Counsellors - Nordahl, Jennifer; Beran, Tanya N.; Dittrick, Crystal J (Canadian Journal of Counselling and Psychotherapy, 2013)
Cyber-bullying is asignificant problem for children today. This study provides evidence of the psychological impact of cyber-bullying among victimized children ages 10 to 17 years (M = 12.48, SD = 1.79) from 23 urban schools in a western province of Canada (N = 239). Students who were cyber-bullied reported high levels of anxious, externalizing, and depressed feelings/behaviours for all types of cyber-bullying they experienced, with girls reporting more severe impact than boys. Strategies are discussed for school counsellors working with youth who have been victimized through electronic means.